PEMANFAATAN GAWAI OLEH GURU BERLATAR BELAKANG NON-PBA DALAM PEMBELAJARAN BAHASA ARAB - Hamidah Hamidah; Adelina Dewi Nuryaman; Muhsinah Muhsinah (Arabi : Journal of Arabic Studies, 2022)
This article aimed to describe the problems of learning Arabic and the use of smartphones to overcome these problems. This qualitative descriptive study examined 11 teachers at a madrasah ibtidaiyah in Central Kalimantan. The data was extracted through observation, interviews, and documentation. To validate the data using the triangulation technique. The data were analyzed by data reduction steps, data presentation, and conclusion drawing. The results showed that the problems of learning Arabic include teachers and students not knowing vocabulary, teachers not being confident in teaching, and students not pronouncing Arabic letters correctly. All teachers try to improve their Arabic language skills using smartphones to overcome these problems. To strengthen the sound of the letters, the teacher often listens to YouTube listening to Arabic script readings, makes videos reading Arabic vocabulary and texts, looks for videos on YouTube that contain engaging Arabic learning, and looks for materials that suit the characteristics of students.